MECHANISM OF ADSORPTION OF WATER VAPOR BY MUSCOVITE: A MODEL BASED ON ADSORPTION CALORIMETRY - Rakhmatkariev G. (My University, 2006)
Adsorption isotherms and differential heats of adsorption of water vapor by muscovite were measured at 303 K. The heats of adsorption are stepwise and each step corresponds to the stoichiometric formation of adsorption complexes of H2O molecules with K+ ions, (H2O)n/K+, (n = 1-6), which are located on the basal and lateral (edge) faces. At saturation, the ditrigonal cavities of the basal faces are fully occupied by hexameric clusters. It is suggested that half of the K+ ions on the basal faces come from neighboring layers by migration under the influence of the adsorbed H2O at the initial stage of adsorption. Similar migration of K+ to the edges was also hypothesized, suggesting that only every second site can be occupied by a cluster. At the final stage of adsorption, H2O molecules are believed to form H-bonded bridges between the hexameric water/cation clusters on the basal faces, whereas on the edge faces no such effect is believed to occur. The mean molar integral adsorption entropy of water is ~-7 J/mol K less than the molar entropy of the bulk liquid. The mobility of H2O on muscovite is slightly less than in bulk water. Migration of K+ cations under the influence of adsorbed H2O both on the basal and lateral faces of muscovite is reversible. Copyright © 2006, The Clay Minerals Society.
Keywords: HEATS OF ADSORPTION; ISOTHERM; MUSCOVITE; POTASSIUM ION; WATER VAPOR